Mitochondrial Phylogenomics Suggests Complex Evolutionary Pattern of Pronotal Foliaceous Mimicry in Hierodulinae (Mantodea: Mantidae), with Description of a New Species of Rhombodera Burmeister, 1838 from China - Qin-Peng Liu; Le Liang; Xin-Yang Zhang; Hao-Kun Li; Chu-Xiang Zhao; Xing-Yue Liu (Insects, 2022)
Hierodulinae is a species-rich mantid subfamily, with some species bearing a notable leaf-like pronotum. However, the evolutionary pattern and taxonomic significance of the leaf-like pronotum are largely unknown. Here, we present a phylogenomic analysis of the Hierodulinae genera Rhombodera Burmeister, 1838, and Hierodula Burmeister, 1838 based on mitochondrial genomes. We also describe a new species, namely Rhombodera hyalina sp. nov. from Guangxi, China. Our phylogenetic result, together with the evidence from male genitalia, suggests the division of the Oriental Hierodula and Rhombodera complex into three clades. We find a complex pattern on the evolution of the leaf-like pronotum, which is present in at least five lineages, respectively, of the above three clades.